Recombination luminescence of radiation defects in NaCl and NaCl-Li crystals at low-temperature elastic deformation - Myasnikova, L.; Shunkeyev, K.; Ubayev, Zh.; Sagimbaeva, Sh.; Kulbatyr, Zh. (Recent Contributions to Physics, 2019)
Using the experimental method of highly sensitive thermoactivation spectroscopy, we studied the spectra of thermally stimulated luminescence (TSL) of purified crystals of NaCl and NaCl-Li under low-temperature (95 K) elastic deformation ( ) in a wide range of the spectrum (200¸850 nm). In the TSL of a NaCl crystal, the dominant peak is an -center, whose intensity doubles during low-temperature deformation and has a maximum of thermal damage at 165–170 K, scanning of which corresponds to the maximum of the TSL spectrum at 3.5 eV. The spectrum of the TSL -peak and the X-ray luminescence coincide and have the same nature – the radiative relaxation of self-trapped excitons upon recombination of mobile holes with electrons. In NaCl-Li TSL, the dominant peaks are F/ and HA (Li) centers, the intensity of which increases 10-fold during low-temperature deformation and having maximum thermal destruction at 110 K and 125 K, respectively. When scanning the TSL spectra at peaks 110K and 125K, we observed radiation with maxima at 2.72 eV and 2.69 eV. An analysis shows that a light lithium cation in the NaCl-Li lattice creates a local deformation as a result of which HA (Li) centers appear. Elastic deformation further stimulates the formation of HA (Li) -centers, evidenced by a 13-fold increase in the intensity of the TSL peak at 125K.